RAGAM LEKSIKON BAHASA JAWA DIALEK TENGGER DAN DIALEK MALANGAN PADA MASYARAKAT DESA PANDANSARI KECAMATAN PONCOKUSUMO KABUPATEN MALANG - Azalia, Maslikhatul Indria; Nurwakhid Muliyono; Ari Nugrahani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the lexical variation of Javanese in the Tengger dialect and Malangan dialect used by the community of Pandansari Village, Poncokusumo District, Malang Regency, and to analyze the social factors influencing the use of both dialects in daily communication. This study employed a descriptive qualitative approach with data collection techniques including observation, semi-structured interviews, documentation, and recordings of community speech in various social contexts. The findings reveal lexical variations consisting of lexicons with identical forms and meanings, lexicons with similar forms but the same meanings, and lexicons with different forms but equivalent meanings. These differences indicate phonological variation and lexical development influenced by social interaction within the community. The Tengger dialect tends to preserve more traditional lexical forms, while the Malangan dialect develops more dynamically in response to social change. The use of both dialects is influenced by age, education, social environment, social mobility, and patterns of community interaction. This study demonstrates that the existence of Tengger and Malangan Javanese dialects functions not only as a means of communication but also as a representation of social identity, group solidarity, and an effort to preserve the local cultural heritage of Pandansari Village.